ORGANIZATIONAL WORK OF THE MILITARY DEPARTMENTS OF THE PARTY COMMITTEES OF THE ALL-UNION COMMUNIST PARTY OF THE NORTH OSSETIAN ASSR DURING THE GREAT PATRIOTIC WAR - Kajtukov, Georgij Borisovic (History, Archeology and Ethnography of the Caucasus, 2021)
The challenges of the time require the application of new methodological principles in the study of numerous issues. This also applies to the history of the Great Patriotic War, which has become the focus of study since the middle of the last century. However, the introduction of a large number of new sources into the scientific discourse makes it possible to highlight gaps that require further study. These issues include the activities of the military departments of the party structure, which became an instrument for organizing the work of the home front. For the first time in regional historiography, the article raises problems of the role of military departments under the party committees of the North Ossetian ASSR. The attracted archival material makes it possible to reconstruct the activities of these bodies during the Great Patriotic War. After their foundation in 1939, they took charge of the military-political education of the citizens of the republic. At that time, their activities were limited to working with the sections of the Society for the Assistance of Defense, Aircraft and Chemical Construction (Osoaviakhim), and the military departments of the Komsomol. However, during the war, the area of their responsibility expanded significantly, as evidenced by the documents. The main directions of work of military departments are considered from the regional and the rural levels. The range of activities included not only assistance to military registration and enlistment offices during the period of mobilization campaigns, participation in the re-certification of citizens liable for military service, but also assistance to families of soldiers of the Red Army, disabled war veterans, fundraising for the construction of tank columns, air units, training militia fighters, fighter battalions, partisan detachments, and air defense forces. After the liberation of the territory of the NO ASSR from the invaders, the task of demining the territory was added to the existing duties of the military departments. Reconstruction of the entire set of activities of military departments will make it possible to expand our knowledge of the history of the Great Patriotic War. In order to eliminate the identified scientific gaps, the article uses a corpus of documents that were previously in limited access. Much attention is paid to the originality of these documents, their informational content. With the help of content analysis, it has been possible to conduct a socio-demographic analysis of the collected material, to study the mechanism of organizing paramilitary formations on the territory of the North Ossetian Autonomous Soviet Socialist Republic.